Morgantina Studies : The Protohistoric Settlement on the Cittadella - Leighton, Robert (Princeton Legacy Library, 2014)
Cover -- Contents -- I. The Excavations -- II. The Finds -- IV. Chronology -- V. The Protohistoric Period -- VI. Catalogue of the Finds.